MENINGKATKAN HASIL BELAJAR PJOK TEKNIK DASAR MENGGIRING BOLA MELALUI PENDEKATAN LAPANGAN - abidin, zainal (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Learning in class IV on PJOK subject matter, Basic Engineering Material, Herding Ball in Soccer Games, mastery of the material is still very low. Of the 20 number of students only 7 students (35%) who achieved the Minimum Completion Criteria (KKM) were set at 6.5 with an average value of 61.5. To overcome the above problems, the steps that need to be implemented are using the approach to field outside the school. In application, the researcher tried on the subject of PJOK about the concept of